HUBUNGAN ANTARA PERAN PENYULUH PERTANIAN DENGAN PARTISIPASI PETANI DALAM USAHATANI PADI HITAM DI KELURAHAN CIKALANG KECAMATAN TAWANG KOTA TASIKMALAYA - Irsyad Padjari; Ristina Siti Sundari; Dona Setia Umbara (Universitas Galuh Ciamis, 2021)
Food is the basic need of human beings, and to fulfill it is our right to secure food. Then lead to safe the food as better nutrition needs and lifestyle. Balck rice can meet both food safety and a healthy lifestyle. The research was conducted to investigate the correlation between agricultural extension role and farmer participation in black rice crops. The method used case study by the amount of sample by Yamane, Isaac, and Michel Formula accordingly. The collected data was primary and secondary data by direct questionnaire and literature study from internet and related institutions. Data analysis used Rank Spearman Test. The result showed a significant correlation and one direction deal with agricultural extension rule and farmer participation in black rice crops. The more agricultural extension rule, the more farmer participation in black rice crops. Black rice consumer was not as much as white rice. Black rice consumer refers to consume deal with healthy lifestyle.